2015
DOI: 10.4049/jimmunol.1402655
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the Three Circulating Monocyte Subpopulations in Human Obesity

Abstract: Three subpopulations of circulating monocytes have been described: CD14(2+)CD16(-) (classical monocytes [CM]), CD14(2+)CD16(+) (intermediate monocytes [IM]), and CD14(+)CD16(2+) (nonclassical monocytes [NCM]). We previously showed that obesity is associated with an increased proportion of IM and NCM. Our objective is to decipher the migratory and inflammatory functions of each monocyte subset in obesity-related low-grade inflammation. Twenty-six healthy, normal-weight and nondiabetic volunteers (C) and 40 obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 42 publications
8
90
2
Order By: Relevance
“…Our data showing elevated macrophage markers expression in the adipose tissue in obesity/T2D are corroborated, at least in part, by other studies as well [2, 22, 23]. Of note, Devevre et al reported three distinct monocytic populations in human obesity named as classical, intermediate, and non-classical monocytes while a 2–4 fold increased expression of TLR4/TLR8 was found in all three subsets [24]. These observations partially support our data showing enhanced TLR8 expression in the obese adipose tissue.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data showing elevated macrophage markers expression in the adipose tissue in obesity/T2D are corroborated, at least in part, by other studies as well [2, 22, 23]. Of note, Devevre et al reported three distinct monocytic populations in human obesity named as classical, intermediate, and non-classical monocytes while a 2–4 fold increased expression of TLR4/TLR8 was found in all three subsets [24]. These observations partially support our data showing enhanced TLR8 expression in the obese adipose tissue.…”
Section: Discussionsupporting
confidence: 91%
“…The white adipose tissue is a site for excessive energy storage and active biosynthesis of adipokines that act via autocrine/paracrine mechanisms in adipocyte-macrophage crosstalk to amplify the local and systemic inflammatory responses in obesity/T2D [25]. The proinflammatory cytokines TNF-α and IL-18 are known to be elevated in obesity/T2D [26, 27] while IL-8 or CXC chemokine ligand (CXCL)-8 is an inflammatory protein and increased circulatory numbers of IL8-expressing monocytes were also reported in human obesity [24]. CRP is a typical systemic inflammatory marker and its increased levels were linked with obesity, blood pressure, and hyperlipidemia [28].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, because of the specific removal of CD16 pos cells by negative selection, the distribution of resultant monocyte subpopulations was very different from PBMCs, consisting almost exclusively of classical monocytes. As intermediate and non‐classical monocytes are believed to have specific functions in vivo , negative selection should not be employed when ex vivo studies require representative monocyte populations. On the other hand, CD14 pos selection may carry the risk of altering the cells' phenotype and potentially induce cell activation .…”
Section: Discussionmentioning
confidence: 99%
“…High expression of the PD1 homologue (PD-1H), which is associated with increased production of TNF, IL-1β, and IL-6, may also contribute to the pro-inflammatory state of these monocytes [44]. CD16+ non-classical and intermediate monocytes have a high migratory capacity, which has been attributed to expression of the chemokine receptors CCR2, CCR5, [45, 46] and CX3CR1 [47]. Indeed, higher expression of the monocyte adhesion molecule CXCL8 was associated with death in SMART [48].…”
Section: Specific Immunologic Pathways That Predict Disease In Hiv Inmentioning
confidence: 99%